X-ray tomographic method to study the internal structure of a TiNi-TiB2 metal matrix composite obtained by direct laser deposition - Korobenkov, Maxim; Lebedev, Mikhail; Promakhov, Vladimir V.; Narikovich, Anton (Materials)
The field of additive manufacturing (AM) of various materials is rapidly developing. At the stage of designing and growing products and for the quality control of finished parts, non-destructive methods of analysis, in particular X-ray computed tomography (CT), are in demand. In addition to the advantages of non-destructive imaging of a wide range of materials in three dimensions, modern CT scanners offer a high contrast and high spatial resolution to provide digital information about their three-dimensional geometry and properties. Within the framework of this article, CT was used to follow the structural evolution of a TiNi–TiB2 metal–ceramic composite obtained by direct laser deposition. The relationship has been established between the additive method of production (layered direct laser deposition) and the formed layered structure of the product in the direction of growth. The porosity of the sample was calculated for each scan direction, and the average for the sample was 1.96%. The matrix of the TiNi–TiB2 composite is characterized by the presence of pores of various sizes, shapes and locations. Spherical voids prevail, but keyhole pores are also found. The heterogeneity of the structure was revealed in the form of clearly traced boundaries of the print layers, as well as differences in the density of the inner and outer regions of the composite.